Implementasi E-Learning Pada Bidang Keahlian Teknologi Informasi dan Komunikasi (TIK) - Pawelangi, Muhammad Rafie; Susetyo, Wismanu (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
The research aims is to reveal the implementation of e-learning on ICT specialization, the factors that affect the interaction between students with teachers, through the evaluation of the effectiveness of online exam, and the learning source. The pupolation used in the research is 2925 students and 31 teachers of SMK in Malang. Resulting from the research in most schools are ready to implement e-learning using applications Moodle, the interaction of teachers and students in the implementation of e-learning is positive and educative. Implementation an online exam is effective.Source of learning materials have traction, and help operate the computer skilled and manage information.In order to keep the sustainability of the implementation of e-learning should be commitment from the school to maintain the stability of the intranet and internet connection, every school need to have special hardware that supports video conference, so interactions that occur are not limited to chat, forums, and email, to avoid leakage of the examination material required a reliable test system and enhance the question bank of the test system, and learning materials should also be prepared in the form of live CDs.